Affective Reactivity in Response to Criticism in Remitted Bipolar Disorder: A Laboratory Analog of Expressed Emotion - Cuellar, Amy K. (2009)
Potential mechanisms to explain the relationship between Expressed Emotion (EE) and poor outcome within bipolar disorder are poorly understood. One possibility is that people with bipolar disorder have difficulty regulating their affect in response to criticism. The present study examined whether participants with bipolar disorder were more affectively dysregulated than control participants when presented with a criticism by a confederate. There was a trend for people with bipolar disorder to react more negatively to the criticism, but there was also evidence that they recovered as quickly as controls. Exploratory analyses found that female gender, the perception of the criticism as more negative, being disabled, and having fewer positive relationships predicted greater reactivity to criticism among people with bipolar disorder.